Assessment of water supply scheme under the infrastructure development program : case study of watharawatta in jaffna district - Vinayagamoorthy, M. (university of Jaffna, 2014)
Access to clean water is a fundamental right of human beings. Good quality water resources are a necessary element for the sustainable development of human beings and the environment. Since the Northern Province has undergone a civil disturbance, the infrastructure facilities were not properly maintained and some part of existing water supply scheme has been damaged as a result of it. After the liberation of the whole Northern Province the Government of Sri Lanka has taken a policy decision to enhance the infrastructure facilities. In the existing watharawatta water supply scheme was implemented by National Water Supply and Drainage Board (NWSDB) to fulfill the need of pipe borne water facility and provide safe drinking water to those who are living within this area. This assessment is an ex post evaluation which is designed to analyze the performance and sustainable effectiveness of the projects based on the Development Assistant Committee (DAC) recommended criteria of relevance, efficiency, effectiveness, impact and sustainability. And by measuring the achievement of the targets at each level and at each strategic goal. Both qualitative evaluation methods such as 'Desk review', 'Depth interview' and 'Focused group discussion' as well as a quantitative survey used for this extensively research. Non probability sampling is used for the data collection. This project clearly shows as the finding the positive impact on the community and villagers. For this reason, this scheme is regarded as the successful project and this Project has contributed to the improvement of access to safe water in Watharawatta. The current system is working in a satisfactory and sustainable way. The success of the project will greatly depend on the quality of support from the government and other agencies to the water users.
Keywords: Sustainable development; Infrastructure facilities; Ex post evaluation